Comprehensive Calculation of Vanadium Redox Flow Battery Capacity For 5kW Lighting Applications - Nadilah Laksmi Marahaini; Feby Agung Pamuji; Vita Lystianingrum Budiharto Putri (International Journal of Marine Engineering Innovation and Research, 2024)
Vanadium Redox Flow Batteries (VRFB) have emerged as a potential solution for renewable energy storage due to their scalability and long lifetime. However, optimizing their operational efficiency and addressing the issue of parameter accuracy for the right load pose significant challenges. This paper aims to quantify the critical parameters of VRFBs and analyze their performance in powering the system under various flow rate operating conditions. Simulations are performed using MATLAB software and unit blocks to evaluate the behavior of VRFBs during discharge and charge conditions at three electrolyte flow rates: 10, 5, and 1 liter per minute (lpm). The analysis focuses on key parameters, including operating duration, charge/discharge time, and state of charge. The results show that higher flow rates increase the discharge duration, while lower flow rates lead to shorter operating times and more pronounced ripples caused by pump control instability and electrolyte density variations. Therefore, designing appropriate parameters in VRFB systems is critical to developing sustainable energy storage solutions and supporting the implementation of clean energy technologies.